(untitled) (Zaporizhzhia Historical Review, 2021)
This article is dedicated to the modern Russian historiography (1991-2000) of the agricultural policy of white guardian’s government with the leaders Denikin and Vrangel all over the controlled Ukrainian territory (1919 – 1920).